2013
DOI: 10.5045/br.2013.48.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Blood group phenotype frequencies in blood donors from a tertiary care hospital in north India

Abstract: BackgroundKnowledge about the frequency of red blood cell-antigen phenotypes in a population can be helpful in the creation of a donor data bank for the preparation of indigenous cell panels and for providing antigen-negative compatible blood to patients with multiple alloantibodies.MethodsABO and RhD blood grouping was performed on 9,280 continuous voluntary and replacement donors. For other rare blood groups, 508 ACD blood samples were obtained from the donors at the Blood Bank of the Department of Transfusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
57
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 11 publications
12
57
6
Order By: Relevance
“… a Fongsarun et al, , b Musa et al, , c Lin et al, , d Broadberry et al, 1994, e Yu et al, , f Makroo et al, , g Agarwal et al, . …”
Section: Resultsmentioning
confidence: 99%
“… a Fongsarun et al, , b Musa et al, , c Lin et al, , d Broadberry et al, 1994, e Yu et al, , f Makroo et al, , g Agarwal et al, . …”
Section: Resultsmentioning
confidence: 99%
“…[13,14] The frequency of Cellano (k) antigen among the donors was 97% as compared to the findings in Sudanese and Indians where the respective prevalence is shown to be 99.6% and 100%. [13,14] The frequency of K-k+ phenotype (81.5%) is found significantly lower among the Saudi donors, as compared to Indians, which was 98.03%. [14] The frequency of Kp a antigen among donors in the blood transfusion services center located in KAMC was 11.7%.…”
Section: Discussionmentioning
confidence: 99%
“…[13,14] The frequency of K-k+ phenotype (81.5%) is found significantly lower among the Saudi donors, as compared to Indians, which was 98.03%. [14] The frequency of Kp a antigen among donors in the blood transfusion services center located in KAMC was 11.7%. It is near frequent to American population (4%), while it is not compatible with Sudanese population (99.8%).…”
Section: Discussionmentioning
confidence: 99%
“…It is well reported that differences in distribution of ABO blood groups exist, both within and among tribal groups of diverse geographical areas of the world [3,[7][8][9][10]. Some variations may even occur within small regions [11]. In Nigeria, The pattern of distribution of the ABO and Rhesus blood varies from region to region as reported in Ogbomosho, south-west region [12], Niger Delta, south-south region [13], Gusau, North-west region [14].…”
Section: Introductionmentioning
confidence: 99%